LIA of Prehistoric Metals in the Central Mediterranean Area: A Review. (7th March 2020) - Artioli, G.; Canovaro, C.; Nimis, P.; Angelini, I.
Abstract : Following animated discussions in the 1990–2010 period concerning the validity and potential application of Pb isotope data to yield information on ancient metallurgy, recently lead isotope analysis has been extensively applied with alternate success and difficulty to the early stages of copper/lead/silver/tin metal flow in the Central Mediterranean area, arbitrarily defined as including Italy, the Mediterranean Islands, and the surrounding regions for comparison purposes. A wealth of data are now available in the literature, many of them interpreted within local contexts and limited geographical extension, and often within a shifting conceptual modeling frame. A brief review of the recently published data indicate that the metal flow in prehistory and protohistory is far more dynamic than presumed on the basis of the traditionally assumed archaeological models. It is suggested that the isotopic tracers, if correctly applied and interpreted, may substantially help in decoding the metal exploitation and trade patterns at different scales, from the local links between mines and smelting sites to wider regional or long‐distance trades. The abundant dataset available are however in need of thorough interpretation in terms of wider archaeological and archaeo‐metallurgical questions, possibly by the use of advanced statistical methods and unconventional data mining protocols.